2012
DOI: 10.1242/dev.068791
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous and symmetric migration of Drosophila caudal visceral mesoderm cells requires dual input by two FGF ligands

Abstract: SUMMARYCaudal visceral mesoderm (CVM) cells migrate synchronously towards the anterior of the Drosophila embryo as two distinct groups located on each side of the body, in order to specify longitudinal muscles that ensheath the gut. Little is known about the molecular cues that guide cells along this path, the longest migration of embryogenesis, except that they closely associate with trunk visceral mesoderm (TVM). The expression of the fibroblast growth factor receptor (FGFR) heartless and its ligands, pyramu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(80 citation statements)
references
References 41 publications
6
74
0
Order By: Relevance
“…As noted earlier, cells in the leading zone are a source of FGF ligands (Aman and Piotrowski, 2008). FGFs serve as migratory cues in a variety of other contexts (Kadam et al, 2012;Vitorino and Meyer, 2008), making them strong candidates for providing a chemoattractive cue for trailing cells. Previous work has already shown that cryptic lamellipodia in trailing cells of the intact PLLp are normally polarized toward the leading edge, and that this polarization is lost upon inhibition of FGF signaling by treatment with the Fgfr1 inhibitor SU5402 (Lecaudey et al, 2008;Sun et al, 1999).…”
Section: Fgfs Mediate Attraction Of Trailing Cells Toward Leading Cellsmentioning
confidence: 86%
“…As noted earlier, cells in the leading zone are a source of FGF ligands (Aman and Piotrowski, 2008). FGFs serve as migratory cues in a variety of other contexts (Kadam et al, 2012;Vitorino and Meyer, 2008), making them strong candidates for providing a chemoattractive cue for trailing cells. Previous work has already shown that cryptic lamellipodia in trailing cells of the intact PLLp are normally polarized toward the leading edge, and that this polarization is lost upon inhibition of FGF signaling by treatment with the Fgfr1 inhibitor SU5402 (Lecaudey et al, 2008;Sun et al, 1999).…”
Section: Fgfs Mediate Attraction Of Trailing Cells Toward Leading Cellsmentioning
confidence: 86%
“…UAS lines utilized for genetic analysis were: UAS .htl. RNAi40627 [Vienna Drosophila Research Center (VDRC); reported to have one off target]; (Dietzl et al, 2007; Kadam et al, 2012)], UAS .htl. RNAi6692 (VDRC; reported to have no off targets), UAS.…”
Section: Methodsmentioning
confidence: 99%
“…Because in other tissues Fgfs act as chemoattractive signals (Sutherland et al, 1996;Sato et al, 2011;Kadam et al, 2012), we considered the possibility that Fgfs also have a more direct role in lateral line cell migration. We analysed the expression of Fgf signalling components and found that after the fusion between the SPCs and primordium, fgf3 and fgf10 are expressed in the leading zone, and fgfr1 in the trailing zone, as previously reported ( , 2008).…”
Section: Fgf Signalling Attracts Spcs Towards the Main Primordiummentioning
confidence: 99%